Branched–linear polyion complexes at variable charge densities. (7th August 2015) - Angelescu, Daniel G; Linse, Per
Abstract: Structural behavior of complexes formed by a charged and branched copolymer and an oppositely charged and linear polyion was examined by Monte Carlo simulations employing a coarse-grained bead–spring model. The fractional bead charge and the branching density were systematically varied; the former between 0 e and 1 e and the latter such that both the comb-polymer and the bottle-brush limits were included. The number of beads of the main chain of the branched copolymer and of the linear polyion was always kept constant and equal, and a single side-chain length was used. Our analysis involved characterization of the complex as well as investigation of size, shape, and flexibility of the charged moieties. An interplay between Coulomb interaction and side-chain repulsion governed the structure of the polyion complex. At strong Coulomb interaction, the complexes underwent a gradual transition from a globular structure at low branching density to an extended one at high branching density. As the electrostatic coupling was decreased, the transition was smoothened and shifted to lower branching density, and, eventually, a behavior similar to that found for neutral branched polymer was observed. Structural analogies and dissimilarities with uncharged branched polymers in poor solutions are discussed.